PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN PRESTASI BELAJAR (Studi Pada Mata Pelajaran Ekonomi Siswa Kelas XI IPS SMA Negeri 2 Kota Pagar Alam) - Novi Herawati; Bambang Sahono (UNIB Press, 2021)
This study aims to describe the application of the student teams achievement division (STAD) type cooperative learning model to improve social skills and student achievement in class XI IPS at SMA Negeri 2 Pagar Alam. The research design used a classroom action research model of Kemmis and Mc. Taggart. The research subjects were 73 students of class XI IPS at SMA Negeri 2 Pagar Alam, consisting of 52 boys and 21 girls. Data collection techniques used observation and test assessment sheets, while the data analysis techniques mean (mean) and percentages and quasi-experimental data analysis with t-test. The results showed that the cooperative learning model type student teams achievement division can improve social skills and economic learning achievement in class XI IPS SMA Negeri 2 Pagar Alam. The implication of the results of this study is that if teachers want to improve social skills and student achievement in Economics, then a cooperative learning model can be used in the type of student teams achievement division (STAD).